Teacher Professional Training: Instructional Practices and Classroom Management - Umar Abdullah (LINGUA: Jurnal Bahasa dan Sastra, 2018)
Abstract: This study explored teachers’ general perceptions about their learning experiences with instructional practices and classroom management gained from teacher professional training, known as PLPG. 149 English teacher participants attending the 2013 PLPG at a public university in Palembang completed a survey questionnaire. Descriptive statistical measures were used to analyze the survey items. Study findings showed that the majority of the teachers perceived PLPG as a vehicle for learning such pedagogical knowledge as instructional practices and classroom management informed by theory and research. Other empirical evidence showed that the teachers argued that (1) continuous professional development, (2) salary increase and incentive, (3) supportive teaching environment, and (4) adequate teaching and learning facilities would sustain quality teaching. This study provided an evaluative account of program effectiveness in providing teacher professional training. Further studies should be undertaken to probe into how teachers translate their learning experience in their routine teaching practices. Keywords: instructional practices; classroom management; teacher professional training; teacher professional development Abstrak: Penelitian ini mengeksplorasi persepsi umum guru tentang pengalaman belajar mereka terkait praktek pembelajaran dan manajemen kelas yang diperoleh dari pelatihan profesi guru yang lebih dikenal sebagai PLPG. Seratus empat puluh sembilan guru bahasa Inggris sebagai peserta PLPG 2013 di salah satu universitas negeri di Palembang melengkapi pertanyaan survei. Analisa respon survei dilakukan dengan pengukuran statistik deskriptif. Hasil penelitian menunjukkan bahwa mayoritas guru menganggap PLPG sebagai sarana m berbagai pengetahuan pedagogis seperti praktek pembelajaran dan manajemen kelas yang sesuai dengan teori dan hasil penelitian. Bukti empiris lainnya menunjukkan para guru menganggap bahwa (1) pengembangan profesi berkelanjutan, (2) kenaikan gaji dan insentif, (3) lingkungan pengajaran yang mendukung, dan (4) fasilitas pengajaran dan pembelajaran yang memadai akan mendukung proses pembelajaran yang berkualitas. Penelitian ini memberikan masukan terkait evaluasi efektivitas program pelatihan profesi guru. Studi lebih lanjut perlu dilakukan untuk mengetahui sejauh mana guru peserta pelatihan profesi guru menerjemahkan pengalaman belajar mereka dalam praktik mengajar sehari-hari. Kata-kata kunci: peraktek pengajaran; manajemen kelas; pelatihan profesi guru, pengembangan profesi guru